ASINKRONISASITRANSFORMASI PRODUKSI DI KABUPATEN SUKOHARJO - Riyardi, Agung (Universitas Muhammdaiyah Surakarta, 2001)
The best economic development is appropriate economical development to community self-identity. The experience of Sukoharjo regency which follow capitalistic national development pattern precisely causes agricultural self-identity of Sukoharjo regency decrease and in the future it will possibly disappear.The strategic and short term solution in overcoming capitalistic development and in returning self identity of Sukoharjo regency are local governmental one-sidedness with agricultural sector. The real implementations of the one-sidedness are agricultural intensification policy, agricultural extensification policy, and product focus policy. From agricultural intensification policy, it is hoped that local government develops the distribution system of welfare agricultural intensification product. From Agricultural extensification policy, local government is hoped make local regulation of lied-idle field using, and from production policy focus of local government of Sukoharjo Regency, it has to focus on outstanding agricultural product so that it creates agroindustry.